2011
DOI: 10.1007/s00373-011-1057-7
|View full text |Cite
|
Sign up to set email alerts
|

Permanental Bounds for the Signless Laplacian Matrix of a Unicyclic Graph with Diameter d

Abstract: Let U n be the set of n-vertex unicyclic graphs, U d n be the set of n-vertex unicyclic graphs of diameter d. In this paper we determine the second-minimum value of signless Laplacian permanent of graphs among U n ; as well we obtain the lower bound for the signless Laplacian permanent of graphs in U d n . The corresponding extremal graphs are characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…on the signless Laplacian permanental polynomials. Li and Zhang [11,12] gave the bounds of constant terms of signless Laplacian permanental polynomials of some graphs. Liu [17] showed that complete graphs and complete bipartite graphs are determined by their signless Laplacian permanental polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…on the signless Laplacian permanental polynomials. Li and Zhang [11,12] gave the bounds of constant terms of signless Laplacian permanental polynomials of some graphs. Liu [17] showed that complete graphs and complete bipartite graphs are determined by their signless Laplacian permanental polynomials.…”
Section: Introductionmentioning
confidence: 99%
“…We call π(L(G), x) (resp, π(Q(G), x)) the Laplacian (resp, signless Laplacian) permanental polynomial of G. e Laplacian permanental polynomial of a graph was first considered by Merris et al [2], and the signless Laplacian permanental polynomial was first studied by Faria [3]. For more studies on (signless) Laplacian permanental polynomials, see [4][5][6][7][8][9][10][11][12][13][14], among others.…”
Section: Introductionmentioning
confidence: 99%
“…For more recent results on Laplacian (resp. signless Laplacian) permanent one is referred to [5,11,12].…”
Section: Introductionmentioning
confidence: 99%